Heteronormative beliefs and internalized homonegativity in the coming out process of Portuguese and Turkish sexual minority men - Torres, C. A. (2021)
Introduction Studies examining why heteronormative beliefs shape the coming out process of sexual minority men are still scarce. This study aimed to examine whether heteronormative beliefs result in more internalized homonegativity and more sexual identity stigma. We also compared socio-cultural contexts—Portugal and Turkey—with distinct social policies toward sexual minority people. Lastly, we explored the correlates of coming out to friends and family members. Methods A cross-sectional study with 562 sexual minority men (93.4% cisgender; Mage = 26.69, SD = 9.59) from Portugal and Turkey was conducted between March and July 2019. Results Heteronormative beliefs were associated with increased internalized homonegativity and, in turn, with increased sexual identity stigma (identity stigma and social discomfort). This mediation was moderated by country, such that conditional direct effects were stronger among Turkish sexual minority men. Conditional indirect effects, however, were stronger among Portuguese sexual minority men. Furthermore, less internalized homonegativity and less social discomfort were associated with coming out to friends and family members in different ways. Conclusions This study contributed to the understanding of sexual identity development and acceptance among sexual minority men in two distinct socio-cultural contexts. Findings showed that the internalization of heteronormative beliefs was associated with identity stigma and highlighted the role of socialization in these processes. Policy Implications For people working with sexual minority men from diverse socio-cultural contexts, our findings can offer new insights on how to offer the best help in the coming out process of these sexual minority men.